1999
DOI: 10.1016/s1074-7613(00)80105-3
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Expression in Early Lymphopoiesis Influences B versus T Lineage Determination

Abstract: Notch receptors regulate fate decisions in many cells. One outcome of Notch signaling is differentiation of bipotential precursors into one cell type versus another. To investigate consequences of Notch1 expression in hematolymphoid progenitors, mice were reconstituted with bone marrow (BM) transduced with retroviruses encoding a constitutively active form of Notch1. Although neither granulocyte or monocyte differentiation were appreciably affected, lymphopoiesis was dramatically altered. As early as 3 weeks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
760
2
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(802 citation statements)
references
References 69 publications
36
760
2
4
Order By: Relevance
“…This variant was used to confirm that effects observed following MAHB expression was ITAM dependent. Both the MAHB and ITAMmutant proteins were cloned into the MIGR1 retroviral vector that expresses a bicistronic mRNA encoding either MAHB or ITAMmutant and GFP (Pui et al, 1999). The retroviral transduction efficiency for each construct was about 50%, as indicated by GFP expression (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This variant was used to confirm that effects observed following MAHB expression was ITAM dependent. Both the MAHB and ITAMmutant proteins were cloned into the MIGR1 retroviral vector that expresses a bicistronic mRNA encoding either MAHB or ITAMmutant and GFP (Pui et al, 1999). The retroviral transduction efficiency for each construct was about 50%, as indicated by GFP expression (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…These mice exhibited a complete block in T-cell development at an early stage of differentiation and an emergence of ectopic B-cell development in the thymus [134]. Conversely, overexpression of constitutive-active Notch (NICD) in the bone marrow instructed a T-cell fate in bone marrow progenitors and inhibited B-cell development [137]. The same effect was observed after overexpression of Delta4 in the thymus [138].…”
Section: T-cell Developmentmentioning
confidence: 99%
“…Thus, T cell development in the thymus is completely blocked in the absence of Notch1 signaling [7]. Moreover, it has been shown that ectopic expression of an activated form of Notch1 in early hematopoietic precursors results in extra-thymic T cell development in the bone marrow [8]. Recently, Schmitt and ZunigaPflĂŒcker developed a culture system whereby the T cell potential of early hematopoietic progenitors can be studied in a simple and quantitative way [9].…”
Section: Introductionmentioning
confidence: 99%